Brill's companion to George Grote and the classical tradition - Dēmētriou, Kyriakos N. (Brill's Companions to Classical Reception, 2014)
George Grote's (1794-1871) extensive publications on ancient Greek history and philosophy remain landmarks in the history of classical scholarship. Since the late 20thcentury, lively interest in the works of Grote has seen his profile revived and his ongoing significance highlighted: he has taken up his rightful place among the most celebrated nineteenth-century classical intellectuals. Grote's critical engagement with Greek historiography and philosophy revolutionized classical studies in his day - a revolution set against both long-established interpretations and prevailing trends in German Altertumswissenschaft. Twenty-first-century scholarship shows that Grote's works remain lively, sparkling and relevant, as they offers valuable insights that cut across the intellectual borders of the Victorian age. His diligent scholarship, fascination with evidence and sound judgement, intertwined with intriguing and insightful narrative prose, continue to captivate the attention of modern readers. In Brill's Companion to George Grote and the Classical Tradition Kyriakos N. Demetriou leads a team of prominent scholars to contextualize, unravel and explore Grote's works as well as provide a critical assessment of his posthumous legacy.